2014
DOI: 10.1002/ejoc.201402130
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of β‐Azolylenamines with Sulfonyl Azides as an Approach to N‐Unsubstituted 1,2,3‐Triazoles and Ethene‐1,2‐diamines

Abstract: The reactions of β‐azolylenamines 1 with sulfonyl azides 2 in acetonitrile furnished 1H‐4‐(azol‐5‐yl)‐1,2,3‐triazoles 3 in yields of 52–93 %. β‐Benzoylenaminones and β‐nitroenamine of type 1 also reacted with tosyl azide to form the same type of products 3, proving the generality and efficiency of the method for the synthesis of N‐unsubstituted 1,2,3‐triazoles. On the other hand, the reactions of 3‐(1‐aryl‐1,2,3‐triazol‐5‐yl)enamines with tosyl azide in the absence of a solvent afforded a mixture of (E)‐1‐dime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 41 publications
0
25
0
Order By: Relevance
“…21 We have found that reactions of NH-triazoles 1a-e with sulfonyl chlorides 2a-d proceed smoothly at room temperature in anhydrous ethanol in the presence of DIPEA (diisopropylethylamine) to afford mixtures of 1-(3a-n) and 2-sulfonyl-4-azolyl-1,2,3-triazoles (4a-n) of various ratios in good yields (Table 1). The formation of 1,5-disubstituted 1,2,3-triazoles 5 was not registered by TLC and NMR spectra.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…21 We have found that reactions of NH-triazoles 1a-e with sulfonyl chlorides 2a-d proceed smoothly at room temperature in anhydrous ethanol in the presence of DIPEA (diisopropylethylamine) to afford mixtures of 1-(3a-n) and 2-sulfonyl-4-azolyl-1,2,3-triazoles (4a-n) of various ratios in good yields (Table 1). The formation of 1,5-disubstituted 1,2,3-triazoles 5 was not registered by TLC and NMR spectra.…”
Section: Resultsmentioning
confidence: 95%
“…3,4 This approach is recognized by many scientists as a powerful method to prepare, starting from 1-sulfonyl-1,2,3-triazoles, a huge variety of other heterocyclic compounds and valuable organic compounds such as azoles, 1 ---M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT Tetrahedron 2 represent a convenient, regioselective and general method to prepare 4-azolyl-1,2,3-triazoles in which these enamines are the synthetic equivalents of azolyl alkynes. 21 Unfortunately, we did not manage to expand our approach to reactions of β-azolyl enamines with sulfonyl azides for the synthesis of 1-sulfonyl-4-azolyl-1,2,3-triazole. The formation of N-unsubstituted-4-azolyl-1,2,3-triazoles took place in high yields instead of the expected 1-sulfonyl-1,2,3-triazoles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The instability of sulfonyl‐substituted triazolines is known, but their disintegration does not necessarily form amidines. For instance, Bakulev and co‐workers reported on the synthesis of 1 H ‐1,2,3‐triazoles via sulfonyl‐substituted triazolines derived from enamines and sulfonyl azides . Furthermore, the collapse of triazolines into amidines may also proceed via different pathways.…”
Section: Methodsmentioning
confidence: 99%
“…We envisioned that the latter two examples have a broad substrate scope and can be used as synthetic precursors for the construction of various amino‐1,2,3‐triazoles. The versatility of these MCRs was further demonstrated by synthesizing 4‐benzoyl‐1,2,3‐(NH)‐triazole 24 by using tosyl azide 23 as nitrogen source . The final step of this reaction was the elimination of N , N ‐dimethyl‐ p ‐toluenesulfonamide.…”
Section: Figurementioning
confidence: 99%